Endoscopic Ultrasound : A New Hope for Patients - Perveen, Shaila; Dhir, Vinay; Paramasivam, Rajesh Kumar; Hossain, Md Rabiul; Ahmed, Mir Azimuddin; Maydeo, Amit (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Endoscopic Ultrasound (EUS) combines endoscopic view and ultrasound images to obtain information about the gastrointestinal tract and the surrounding tissues and organs in abdomen and mediastinum. Placing the transducer on the tip of an endoscope allows it to get close to the organs inside the body. The EUS can also obtain information about the layers of the intestinal wall as well as adjacent areas such as lymph nodes and the blood vessels. It can study the flow of blood inside blood vessels using Doppler ultrasound and obtain tissue samples by passing a FNA needle into enlarged lymph nodes or suspicious tumors. Staging of cancer is becoming an important use of EUS. It can provide information regarding the depth of penetration and spread of cancer to adjacent tissues and lymph nodes, useful for staging. Interventional EUS offers durable analgesia for palliation and minimally invasive drainage procedures which does not result in cutaneous fistulae. In future, Interventional EUS will open up a new frontier hence further improving the contributory role of GI endoscopy. Our aim was to evaluate the role of endoscopic ultrasound (EUS) in literatures of the past 3 decades as diagnostic and therapeutic aid based on original articles (randomized controlled trials, prospective and retrospective studies), meta-analyses, reviews and surveys pertinent to gastrointestinal EUS. MEDLINE and PubMed search (1984-2013) were conducted using Endoscopic Ultrasound for re-trieving pertinent studies and arranged according to equipment introduction, uses, procedures, advantage, disadvantage, complications, therapeutic applications and limitations of EUS. Figures included are taken during performance of the EUS procedures at the institute. J Bangladesh Coll Phys Surg 2015; 33(1): 23-31